Gerenciamento de migração de plataforma de software: análise da melhoria da qualidade de serviço prestado pela área de Service Desk após migração do Software Otrs para o Sofware Webassist. Estudo de caso da empresa XYZ. - Oliveira, Paulo Roberto de (Universidade do Vale do Rio dos Sinos, 2016)
In a market extremely competitive, where even high technology products will soon become a commodity, where quality is no longer a differential, the process of post-sale becomes the most important point to ensure the company the maintenance of its customers, entering new markets and its prominence in the same ones. Due to the need to reduce costs, the industries started to use outsourced service to technical assist their products in the field, and this has led to a sharp drop in the quality of the services offered. Ensure quality of labor, availability of parts and pieces for refitting, efficiency of the assistance provided is the great challenge within this scenario. This article presents an analysis based on BPM - Business Process Management for the replacement of a management system of (technical) assistance, on the other hand more closely aligned with the company's expectations, and actions for improvement of support infrastructure, through techniques of data collection and analysis.
Keywords: Gestão de processos; Migração de sistema; BPM; Service desk; Management of processes; Migration of system